2022
DOI: 10.1021/acsami.1c19916
|View full text |Cite
|
Sign up to set email alerts
|

Emulation of Synaptic Plasticity on a Cobalt-Based Synaptic Transistor for Neuromorphic Computing

Abstract: Neuromorphic computing (NC), which emulates neural activities of the human brain, is considered for the low-power implementation of artificial intelligence. Toward realizing NC, fabrication, and investigations of hardware elementssuch as synaptic devices and neuronsare crucial. Electrolyte gating has been widely used for conductance modulation by massive carrier injections and has proven to be an effective way of emulating biological synapses. Synaptic devices, in the form of synaptic transistors, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Song et al have reported simulation-based on-chip learning in ANNs using experimentally obtained synaptic characteristic in a skyrmionic device . But the remaining experimental spintronic studies only show device-level data (without any system-level simulation based on the device data), ,, or show training of an SNN or some other biologically motivated network ,, (which is different from an ANN and does not use LTD and LTP of a synapse the way an ANN does), or use binary spintronic synapses/magnetic tunnel junctions (MTJs) , as opposed to the multibit synapses we focus on here (one device stores 5 bits in our case).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al have reported simulation-based on-chip learning in ANNs using experimentally obtained synaptic characteristic in a skyrmionic device . But the remaining experimental spintronic studies only show device-level data (without any system-level simulation based on the device data), ,, or show training of an SNN or some other biologically motivated network ,, (which is different from an ANN and does not use LTD and LTP of a synapse the way an ANN does), or use binary spintronic synapses/magnetic tunnel junctions (MTJs) , as opposed to the multibit synapses we focus on here (one device stores 5 bits in our case).…”
Section: Introductionmentioning
confidence: 99%
“…Nanomagnetic and spintronic devices based on the heavy-metal-ferromagnetic-metal-oxide heterostructures have been considered very attractive for various applications including nonvolatile memory (NVM), logic, and neuromorphic computing. These devices heavily use interfacial phenomena like perpendicular magnetic anisotropy (PMA) and spin–orbit torque (SOT) for their functionalities. , PMA is considered to originate primarily from the ferromagnet–oxide interface, , while the following mechanisms have been considered as origins of SOT: Spin Hall effect inside the heavy metal leads to accumulation of spin-polarized electrons at the heavy-metal–ferromagnet interface; these spin-polarized electrons subsequently flow from the heavy metal to the ferromagnet to apply SOT on the magnetic moments of the ferromagnetic layer. ,, Rashba effect at the heavy-metal–ferromagnet interface Additional interface-originated effects like the orbital Rashba–Edelstein effect, recently reported by Chen et al …”
Section: Introductionmentioning
confidence: 99%
“…Synaptic functions have been emulated in two-terminal devices such as phase change memory, , resistive random-access memory, atomic switches, , magnetoresistive random-access memory, , and in three-terminal devices such as electrolyte-gated transistors (EGTs), and ferroelectric field effect transistors. Of the various EGTs, proton-gated transistors are considered to be one of the core elements for building physical neural networks because of their favorable characteristics, such as low power consumption (down to aJ), smaller charge carriers, faster operation, and compatibility with flexible electronics. , In these devices, organic and inorganic electrolytes such as chitosan, Nafion, and mesoporous silica (MSC) have been used as the gate electrolyte, which acts as proton (H + ) conductors and reservoirs. , Protons with an ionic radius of 0.04 Å have a higher diffusion rate than other ions, leading to faster operation of EGTs by interfacial ionic effects such as proton insertion and extraction without affecting the stability of the channel material. , Several groups have shown various synaptic behaviors in chitosan-based EGTs with an indium–tin-oxide (ITO) or indium–zinc-oxide (IZO) channel, , Nafion-based EGTs with a poly­(3,4-ethylene-dioxythiophene): polystyrenesulfonate (PEDOT:PSS) or tungsten oxide (WO 3 ) channel, ,, and MSC-based EGTs with an ITO channel. , Note that synaptic functions can be achieved in transistors without the use of electrolytes or ferroelectric gates, as recently demonstrated by Dai et al…”
Section: Introductionmentioning
confidence: 99%
“…This limitation represents an incomplete implementation of biological synapses in two-terminal devices. In contrast, a three-terminal synaptic device can simultaneously learn and transmit signals through different parts, the gate terminal and the channel, respectively [ 20 ]. As a result, synaptic behavior can be fully emulated by a three-terminal device.…”
Section: Introductionmentioning
confidence: 99%